Go green parking / Amierul Azim Azali and Faizul Hafizi Ahmad - Azali, Amierul Azim; Ahmad, Faizul Hafiz (2015)
The majority of parking system today open all lights at the parking spaces at night either have car or vice versa. This system had use a lot of electrical energy that will harm the world and also need higher cost in order to maintain the system. Because of that, the project 'Go Green Parking' is proposed. 'Go Green Parking' is a project that will switch on the light in the parking space at night or when low light intensity. This project is very helpful in order to save electrical energy. With 'Go Green Parking', each parking space is equipped with a switch to switch on light at night or when low light intensity automatically if there are any vehicles park at the parking spaces. To conclude that, with the invented of Go Green Parking, it will reduce the usage of electrical energy that is extremely important to human. Because of this also, the effect of excessive usage of electrical energy will be reduce. After that, nowadays with the bad economy that people have to face, Go Green Parking system is one of the things that should have done because it can cut the budget and at the same time will prevent from future destruction because the limited electrical energy supply. Therefore Go Green Parking is more effective and economic than a usual parking system as it can minimize the usage of electrical energy.